Spatiotemporal trends and factors influencing online attention for China’s tea industry - Shu, Rentian; Xiao, Jingyi; Su, Zhucheng (Frontiers in Environmental Science, 2023)
Abstract: In the context of the "Internet plus" era, the study of tea industry network attention is a new perspective in research on the tea industry and an opportunity for the sustainable and high-quality development of this industry. Based on the Baidu index, this paper obtains web attention data from 2012 to 2021, analyzes the spatial and temporal evolution characteristics of network attention using the seasonal concentration index and geographic concentration index, and quantitatively discusses the influencing factors using correlation analysis and GeoDetector. The results show the following: (1) The interannual change in China's tea industry network attention shows "rapid growth, high level of stability, slow decline," the monthly distribution has an intense concentration, mainly in March-April and October, and the interday distribution of attention peaks on weekdays. (2) The spatial distribution shows an intense geographical concentration, with an overall trend of "light concentration first, then light dispersion." The migration trajectory of the center of attention is tilted toward the southwest. (3) Economic development status, residents' income, the natural environment of tea growing, the leisure time of followers, and the price level of tea are the essential factors affecting the attention of the tea industry network. In contrast, other factors have a weak influence on attention.